Detection of point mutations on 23S rRNA of Helicobacter pylori and resistance to clarithromycin with PCR-RFLP in gastric biopsy specimens in Mersin, Turkey - Orhan SEZGİN and Gönül ASLAN and Engin ALTINTAŞ and Seda TEZCAN and Mehmet Sami SERİN and Gürol EMEKDAŞ (Turkish Journal of Gastroenterology, 2019)
-